Microbial Diversity in the Eukaryotic SAR Clade: Illuminating the Darkness Between Morphology and Molecular Data. (7th March 2018) - Grattepanche, Jean‐David; Walker, Laura M.; Ott, Brittany M.; Paim Pinto, Daniela L.; Delwiche, Charles F.; Lane, Christopher E.; Katz, Laura A.
Abstract : Despite their diversity and ecological importance, many areas of the SAR—Stramenopila, Alveolata, and Rhizaria—clade are poorly understood as the majority (90%) of SAR species lack molecular data and only 5% of species are from well‐sampled families. Here, we review and summarize the state of knowledge about the three major clades of SAR, describing the diversity within each clade and identifying synapomorphies when possible. We also assess the "dark area" of SAR: the morphologically described species that are missing molecular data. The majority of molecular data for SAR lineages are characterized from marine samples and vertebrate hosts, highlighting the need for additional research effort in areas such as freshwater and terrestrial habitats and "non‐vertebrate" hosts. We also describe the paucity of data on the biogeography of SAR species, and point to opportunities to illuminate diversity in this major eukaryotic clade. See also the video abstract here:https://youtu.be/_VUXqaX19Rw . Abstract : Despite their diversity, abundance, and importance, fewer than 10% of the species within the SAR—Stramenopila, Alveolata, and Rhizaria—clade have been assessed using molecular tools. Only a small percentage of the molecular records contain information on ecology or have associate location data, indicating a tremendous dark area.